PENANAMAN KARAKTER RELIGIUS DALAM PELAKSANAAN PROGRAM JUM’AT BERGEMA DI SMA NEGERI 2 SU - Idris, Gusti (Jurnal Pembelajaran Prospektif, 2019)
The purpose of this study was to determine the religious character in the implementation of the Friday Program in SMA Negeri 2 Sungai Raya. This research uses a qualitative approach. The location of research in SMA Negeri 2 Sungai Raya. The results of the study showed that: implementing religious character of the Friday Program was not only read the Letter of Yasin, Asmaul Husna, Youth Tausiah, and prayer but through the process of carrying out activities accustomed, which in turn can lead to religious attitudes in students in everyday life. The manifestation of religious values that can be seen from theimplementation of the Reverberating Friday Program are among others (a) theemergence of religious insights in communicating and speaking in public, (b) observing the devout prayer in congregation at the mosque, carrying out the Dhuha prayer or sunnah prayer, dhikr after prayer, (c) the establishment of faith and devotion through participation in religious activities such as MABIT (night of religious and devotion), echoes of the Prophet's prayer, recitation, Commemoration of the new year AD, commemoration of the Prophet's Birthday, (d) always remembering Allah by dhikr after prayer, grave pilgrimage, takziah, natural tadabur, (e) having good morals are manifested in the behavior of visiting members who are sick, helping those who are struck down by calamities or disasters, establishing fraternity and friendship.